VO #015 Revised proposal of 500mm Dia bored pile works rev. 01 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding VO #015 revised proposal of 500mm Dia bored pile works rev. 01k of BRAC University new campus project.